2022
DOI: 10.47391/jpma.3053
|View full text |Cite
|
Sign up to set email alerts
|

Genetic profiles of different ethnicities living in Karachi as regards to tobacco-metabolizing enzyme systems and the risk of oral cancer

Abstract: Objective: To detect polymorphisms of CYP1A1, GSTM1 and GSTT1 gene loci among various tobacco-consuming ethnicities in an urban centre, and to relate these with susceptibility to oral cancer. Method: The cross-sectional, case-control study was conducted at Ziauddin University, Karachi, and the Dow University of Health Sciences, Karachi, from 2011 to 2016, and comprised patients having oral squamous cell carcinoma in group A, with oral precancerous lesions in group B, and tobacco habit-matched controls in group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Another factor to consider is that Pakistan is a multi-ethnic country, and the distribution of tobacco-metabolising enzymes also varies significantly among different populations [26]. More research needs to be conducted on the genetic predilection of Pakistanis to the disease and oral surgeons should practice extreme vigilance.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Another factor to consider is that Pakistan is a multi-ethnic country, and the distribution of tobacco-metabolising enzymes also varies significantly among different populations [26]. More research needs to be conducted on the genetic predilection of Pakistanis to the disease and oral surgeons should practice extreme vigilance.…”
Section: Discussionmentioning
confidence: 99%
“…The risk was significantly higher than when any of these genotypes were present individually. Another study conducted by Alamgir et al [26] found that the distribution of tobacco-metabolising enzymes varied amongst populations of different ethnicities.…”
Section: Genetic Predisposition To Developing Ocmentioning
confidence: 98%
See 1 more Smart Citation